Analisis Strategi Pengembangan Bisnis Jasa Konstruksi (Studi Kasus: PT Tri Manunggal Karya) - Firmansyah, Hilal; Daryanto, Heny K; Syarief, Rizal (Jurnal Manajemen, 2022)
Increasing competition of construction business in Indonesia forces PT Tri Manunggal Karya (PT TMK) to innovate to survive in the construction industry. One way is by having a competitive strategy for its business development. As a holding company, a proper strategy is highly required by PT TMK to open up market opportunities for the company and its subsidiaries and to avoid the risk of business failure and financial losses. This study aims to analyze internal and external factors and analyze the priority strategies for PT TMK development. The analytical methods used were Internal Factor Evaluation (IFE) Analysis, External Factor Evaluation (IFE) Analysis, Strength, Weakness, Opportunity, and Threats (SWOT) Analysis, Analytical Hierarchy Process (AHP) Analysis. The result shows that the external condition of PT TMK is in a high position in responding to opportunities and threats. Its internal figures are in a strong stand in utilizing strengths and overcoming its weaknesses. Opportunity in the company's industry can be concluded because infrastructure development and competent human resources are still limited in the Eastern parts of Indonesia. The threats are post-pandemic conditions and fast-growing construction technology. The result of the Analytical Hierarchy Process (AHP) shows the strategy of acquiring new business units is considered as the main priorities, followed by expansion out of Java Island.